Effect of multiorgan abdominal ischemic preconditioning on experimental kidney transplantation - Juan Cruz Abate; Ivana Ivanoff Marinoff; Nathalie Arnal; Mariana Machuca; Rodrigo Papa-Gobbi; Leandro Vecchio; Martín Rumbo; Pablo Stringa; Natalia Raquel Lausada (Acta Cirúrgica Brasileira)
ABSTRACT Purpose: To mitigate ischemia-reperfusion injury (IRI) triggered in solid organ transplant procedures, we aimed to evaluate the effects of multi-organ abdominal ischemic preconditioning (MAIP) in the context of renal IRI. Methods: An experimental kidney transplant model was conducted. Rats were divided into three groups: an intervention free basal group from which physiological data was collected; a control group (CT), which consisted of transplanted animals without MAIP; and a treated group, in which a MAIP protocol was implemented in the donor during the procurement of the left kidney, monitoring the recipient for 24 hours. Results: Urea, creatinine, and lactate dehydrogenase, as well as histopathological analysis (Banff: CT 1,66 ± 0,57 vs. basal 0, and MAIP 1), showed a clear trend in favor of MAIP group. Similar results were observed for tumor necrosis factor-α, interleukin-6 and CXCL10, as well as indicators of oxidative stress, with statistically significant levels for CXCL10 [0,295 ± 0,0074 arbitrary units (AU) CT and 0,0057 ± 0,0065 AU MAIP] and TBARS (2,93 ± 0,08 nmol/μg CT; and 2,49 ± 0,23 nmol/μg MAIP; p 0.05). Conclusion: The findings indicated that the MAIP exerts a protective influence on the transplanted kidneys, functioning as an IRI-protective strategy and enhancing the parameters associated with renal graft functionality.